Quality of life scales for patients with gastroesophageal reflux disease: A literature review - Xiao-Li Guan; Hui Wang (Elsevier, 2015)
Gastroesophageal reflux disease (GERD) is a common chronic disease of the gastrointestinal tract that occurs in 3.1% of the Chinese population [1]. Heartburn, acid regurgitation and epigastric pain are typical clinical symptoms of GERD. These symptoms can affect patients' work productivity, sleep, diet and daily activities, thus resulting in a reduced quality of life (QOL) [2]. Although patient QOL is increasingly being considered as a medical outcome index in the evaluation of the impact of GERD symptoms on patients' health status, measuring patient QOL in clinical trials can be challenging due to the lack of a standard assessment tool. Therefore, we aim to review the commonly used generic, disease-specific and hybrid QOL questionnaires to evaluate patients with GERD to provide a reference for clinical nursing work.